"Devilish Money" and Peasant Ethics: Leo Tolstoy's Economic Imagination and Emplotment in "Polikushka". Issue 1 (January 2017) - VDOVIN, ALEXEY
Abstract : The article investigates how Leo Tolstoy's economic ideas are embodied and instantiated in the plot of his short story "Polikushka" (1863) from the two intertwined perspectives of narratology and the history of economic ideas. The various names given to the sum of money the protagonist, Polikei, loses can be explained by the ruble's "dual exchange rate"; that is, the differential rates between the silver ruble and assignation ruble (1:3.5) which existed in Russia from 1839 to 1851. Polikei's misplacement of banknotes (called "devilish" in "Polikushka" drafts) accords with the broader European literary mythology of banknotes as the Devil's playthings. In addition to European parallels, the article discusses possible Russian plot sources dating back to Nekrasov's poetry and the prose of Pogodin, Potekhin, and Dostoevsky. In the second section, the article explores the narrative patterns of the story and demonstrates that we cannot blame Polikei's death on his mistress' desire to test and rehabilitate him. The narration is organized as a network of mutually exclusive viewpoints, the correlation of which develops into an ugly portrayal of both the elderly landlady and Polikei, shown to be equally guilty in the tragic ending of the story. In the last two sections, the article reveals the ideological underpinnings of Tolstoy's skeptical attitude, displayed in his pedagogical writings of 1861–62, toward the notion of peasants and the educated elite being able to communicate with each other effectively. In these writings Tolstoy noted the harmful effects that philanthropy, mis‐targeted education, false ideologies, and the unreasonable circulation had on the peasantry. In conclusion, the article locates one possible source for Tolstoy's viewpoint in the political and economic ideas of P.‐J. Proudhon, with whom Tolstoy communicated in Brussels when writing "Polikushka."